2004
DOI: 10.1016/j.febslet.2004.07.087
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid‐induced quenching of the phycobilisome fluorescence in photosystem II‐deficient mutant of Synechocystis sp.

Abstract: Brief -10-second long -irradiation of a photosystem II-deficient mutant of cyanobacterium Synechocystis sp. PCC 6803 with intense blue or UV-B light causes an about 40% decrease of phycobilisome (PBS) fluorescence, slowly reversible in the dark. The registered action spectrum of PBS fluorescence quenching only shows bands at 500, 470 and 430 nm, typical of carotenoids, and an additional UV-B band; no peaks in the region of chlorophyll or PBS absorption have been found. We propose that quenching induced by caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
105
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 27 publications
5
105
0
1
Order By: Relevance
“…By increasing the thermal dissipation of the absorbed energy, OCP decreases energy arriving at the photosynthetic reaction centers (Wilson et al, 2006). This photoprotective mechanism is activated by blue-green light but not by orange or red light, which are not absorbed by OCP (Rakhimberdieva et al, 2004;Wilson et al, 2006). OCP has an a-helical N-terminal domain (residues 15 to 165) and an a/b C-terminal domain (residues 190 to 317).…”
Section: Introductionmentioning
confidence: 99%
“…By increasing the thermal dissipation of the absorbed energy, OCP decreases energy arriving at the photosynthetic reaction centers (Wilson et al, 2006). This photoprotective mechanism is activated by blue-green light but not by orange or red light, which are not absorbed by OCP (Rakhimberdieva et al, 2004;Wilson et al, 2006). OCP has an a-helical N-terminal domain (residues 15 to 165) and an a/b C-terminal domain (residues 190 to 317).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the mechanism of thermal energy dissipation in cyanobacteria, which plays a key role in global carbon cycling, remained elusive. Only within the last few years has a photoprotective mechanism associated with the soluble phycobilisome antenna of PSII in cyanobacteria been demonstrated (8)(9)(10)(11)(12)(13)(14). A specific soluble carotenoid protein, the orange carotenoid protein (OCP), plays an essential role in this process (9,10).…”
mentioning
confidence: 99%
“…It has been recently shown that, in cyanobacteria, like in plants, there exists a photoprotective process that decreases the energy transfer between the antenna and the reaction centers by increasing thermal dissipation (8)(9)(10)(11)(12)(13). However, this mechanism is not triggered by a lowering of the luminal pH, as occurs in plants;…”
mentioning
confidence: 99%